Optimum Nitrogen Dose and its use efficiency of a Bacterial Blight Disease Resistant Rice ALART Material in Chhiata Clay Loam Soil (Bangladesh Rice Journal, 2026)
Given the wide spread deficiency of nitrogen in Bangladesh, its optimum dose of advance breeding lines need to be determined before releasing as a variety. Field experiment was conducted with advance line BR8938-19-4-3-1-1-P2-HR3 (BBRAL) using BRRI dhan28 as susceptible check. Both the genotypes received six nitrogen doses – 0 to 200 kg N ha-1 with an interval of 40 kg ha – 1 from urea in a split-plot design. Both the tested genotype received flat standard doses of P, K, S and Zn. Quadratic regression model was used to determine optimum N requirement. Quadratic equations ŷ = 3.46 + 0.04N – 0.00013N2, (R2 = 0.95, p = 0.006) for the bacterial blight resistant line BR 8938-19-4-3-1-1-P2-HR3, and ŷ = 3.73 + 0.04N – 0.00012N2, (R2 = 0.99, p = 0.006) for the check variety BRRI dhan28 explained the relationship for N rates and estimated grain yield. The calculated economic optimum N dose using quadratic regression model for BBDRL and the susceptible check BRRI dhan28 was 153 and 162 kgNha-1, respectively. The application of 153 and 162 kg N ha-1 predicted the estimated yield of 6.81 and 7.21 for the advanced line and BRRI dhan28, respectively. Nutrient use efficiencies such as agronomic use efficiency, apparent recovery of applied N, internal use efficiency and nitrogen harvest index of the tested advance line were similar to those of BRRI dhan28.Bangladesh Rice J.28(1): 81-90, 2024